Association Between Dietary Fiber Intake and Bone Loss in the Framingham Offspring Study. (7th November 2017) - Dai, Zhaoli; Zhang, Yuqing; Lu, Na; Felson, David T; Kiel, Douglas P; Sahni, Shivani
ABSTRACT: Dietary fiber may increase calcium absorption, but its role in bone mineralization is unclear. Furthermore, the health effect of dietary fiber may be different between sexes. We examined the association between dietary fiber (total fiber and fiber from cereal, fruits, vegetables, nuts, and legumes) and bone loss at the femoral neck, trochanter, and lumbar spine (L2 to L4 ) in older men and women. In the Framingham Offspring Study, at baseline (1996–2001), diet was assessed using the Willett food‐frequency questionnaire, and bone mineral density (BMD) was measured using dual‐energy X‐ray absorptiometry. Follow‐up BMD was measured in 2001–2005 and 2005–2008 among 792 men (mean age 58.1 years; BMI 28.6 kg/m 2 ) and 1065 women (mean age 57.3 years; BMI 27.2 kg/m 2 ). We used sex‐specific generalized estimating equations in multivariable regressions to estimate the difference (β) of annualized BMD change in percent (%ΔBMD) at each skeletal site per 5 g/d increase in dietary fiber. We further estimated the adjusted mean for bone loss (annualized %ΔBMD) among participants in each higher quartile (Q2, Q3, or Q4) compared with those in the lowest quartile (Q1) of fiber intake. Higher dietary total fiber (β = 0.06, p = 0.003) and fruit fiber (β = 0.10, p = 0.008) was protective against bone loss at the femoral neck in men but not in women. When examined in quartiles, men in Q2–Q4 of total fiber had significantly less bone loss at the femoral neck versus those in Q1 (all p < 0.04). For women, we did not observe associations with hip bone loss, although fiber from vegetables appeared to be protective against spine bone loss in women but not men. There were no associations with cereal fiber or nut and legume fiber and bone loss in men or women. Our findings suggest that higher dietary fiber may modestly reduce bone loss in men at the hip. © 2017 American Society for Bone and Mineral Research.